Development of Volleyball Physical Condition Test Application for Collage Students - Zuhair, Najmi Alvin; Hartati, Hartati; Usra, Meirizal (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research aims to develop a valid and practical application for physical condition tests in volleyball. Research refers to the Borg and Gall development model which consists of ten stages: potential and problem, data collection, product design, product validation, product revision, product trial, product revision, product usage trial, product revision, and ends with mass production. Data was collected using validation sheets and questionnaires. This physical condition test app has been validated by experts with 4.20 in the highly valid category. Product trials showed a practicality level of 3.40 very good categories, then product usage tests showed practical results of 3.79 in category very good. The results showed that the use of physical condition test applications that have been developed is practically used to facilitate the collection and storage of physical condition test result data. Users are advised to use a physical condition test application when performing the test to get accurate test results.